47.5k views
2 votes
Does anyone know the answers???

Does anyone know the answers???-example-1
User Nucleon
by
5.4k points

2 Answers

5 votes

Answer:

Answer for number 17.

Explanation:

Simplifying

6(x + 4) = 3(4x + -2)

Reorder the terms:

6(4 + x) = 3(4x + -2)

(4 * 6 + x * 6) = 3(4x + -2)

(24 + 6x) = 3(4x + -2)

Reorder the terms:

24 + 6x = 3(-2 + 4x)

24 + 6x = (-2 * 3 + 4x * 3)

24 + 6x = (-6 + 12x)

Solving

24 + 6x = -6 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.

24 + 6x + -12x = -6 + 12x + -12x

Combine like terms: 6x + -12x = -6x

24 + -6x = -6 + 12x + -12x

Combine like terms: 12x + -12x = 0

24 + -6x = -6 + 0

24 + -6x = -6

Add '-24' to each side of the equation.

24 + -24 + -6x = -6 + -24

Combine like terms: 24 + -24 = 0

0 + -6x = -6 + -24

-6x = -6 + -24

Combine like terms: -6 + -24 = -30

-6x = -30

Divide each side by '-6'.

x = 5

Simplifying

x = 5

User Vdsf
by
5.2k points
1 vote

Answer:

16:3

17:4

18:1

19:1

Explanation:

User Evan Closson
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.